Rapidly declining fine-scale spatial genetic structure in female red deer. - Nussey, D; Coltman, D; Coulson, T; Kruuk, L; Donald, A; Morris, S; Clutton-Brock, T; Pemberton, J (2005)
A growing literature now documents the presence of fine-scale genetic structure in wild vertebrate populations. Breeding population size, levels of dispersal and polygyny--all hypothesized to affect population genetic structure--are known to be influenced by ecological conditions experienced by populations. However the possibility of temporal or spatial variation in fine-scale genetic structure as a result of ecological change is rarely considered or explored. Here we investigate temporal variation in fine-scale genetic structure in a red deer population on the Isle or Rum, Scotland. We document extremely fine-scale spatial genetic structure (< 100 m) amongst females but not males across a 24-year study period during which resource competition has intensified and the population has reached habitat carrying capacity. Based on census data, adult deer were allocated to one of three subpopulations in each year of the study. Global F(ST) estimates for females generated using these subpopulations decreased over the study period, indicating a rapid decline in fine-scale genetic structure of the population. Global F(ST) estimates for males were not different from zero across the study period. Using census and genetic data, we illustrate that, as a consequence of a release from culling early in the study period, the number of breeding females has increased while levels of polygyny have decreased in this population. We found little evidence for increasing dispersal between subpopulations over time in either sex. We argue that both increasing female population size and decreasing polygyny could explain the decline in female population genetic structure.